'Bombable geographies' and the international Monroe: a global south history of the unwilling or unable standard - Gurmendi Dunkelberg, Alonso (Journal on the use of force and international law, 2024)
This article argues that the history of the Unwilling or Unable Standard has been misunderstood, usually framed as either a longstanding principle or a recent, modern innovation in the context of the War on Terror. In taking a Global-South-centred approach to history, this article concludes that it is neither. Instead, it is framed as an imperial logic that emerges and submerges from history, depending on whether imperial and colonial powers need to determine specific geographies as 'bombable'. The article finds key similarities between the Unwilling or Unable of today and the Monroe Doctrine of the early twentieth century, concluding they are manifestations of the same imperial logic in a history of discontinuity. The article concludes that in a South-centred history, the use of force rules is not expansive, but rather that non-Western states have consistently defended a much more anti-interventionist international law than Eurocentric history might otherwise suggest.